2020
DOI: 10.1108/pr-06-2019-0323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of union commitment on job performance in China

Abstract: PurposeThis study aims to reveal the mechanism through which union commitment influences job performance in China, focusing on the mediating role of employee participation and the moderating role of affective commitment.Design/methodology/approachIn this study, a cross-sectional design was employed to collect data from 596 union members in 33 unionized enterprises in China's Pearl River Delta region.FindingsThe results demonstrate that union commitment is positively related to both employee participation and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Currently, only two of the three variables mentioned have been examined in prior research. For example, a number of studies have shown that employee performance is the result of organizational commitment (Indarti, Solimun, Fernandes, & Hakim, 2017;Huang, Yuan, Shen, & Li, 2020;AlMazrouei & Zacca, 2021). Furthermore, as of November 28, 2020, few studies on employees had been published in COVID-19-related organizational behavior papers.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only two of the three variables mentioned have been examined in prior research. For example, a number of studies have shown that employee performance is the result of organizational commitment (Indarti, Solimun, Fernandes, & Hakim, 2017;Huang, Yuan, Shen, & Li, 2020;AlMazrouei & Zacca, 2021). Furthermore, as of November 28, 2020, few studies on employees had been published in COVID-19-related organizational behavior papers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a less conservative cutoff value of 0.80 has also been used for TLI (e.g. Cui et al , 2020; Felicio et al , 2015; Glazer and Beehr, 2005; Huang et al , 2020; Schreurs et al , 2020). Given the large number of indicators (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A good and effective exploration needs a transparent management plan (Saunders et al, 2009) that captures thoroughly the universal realities (Huang et al, 2020). Accordingly, we selected quantitative methods for this study.…”
Section: Design and Respondentsmentioning
confidence: 99%